The use of encapsulated condensed tannin extract and β-carotene supplementation to manipulate oxidative status, production and reproduction performance in sheep - Hassen, Abubeker (University of Pretoria, 2023)
Thesis (PhD (Animal Science))--University of Pretoria, 2022.